Impact of the CTLA‐4/CD28 axis on the processes of joint inflammation in rheumatoid arthritis. Issue 1 (27th December 2012) - Körmendy, Dezsö; Hoff, Holger; Hoff, Paula; Bröker, Barbara M.; Burmester, Gerd‐Rüdiger; Brunner‐Weinzierl, Monika C.
Abstract Objective The importance of the costimulatory molecules CD28 and CTLA‐4 in the pathologic mechanism of rheumatoid arthritis (RA) has been demonstrated by genetic associations and the successful clinical application of CTLA‐4Ig for the treatment of RA. This study was undertaken to investigate the role of the CTLA‐4/CD28 axis in the local application of CTLA‐4Ig in the synovial fluid (SF) of RA patients. Methods Quantitative polymerase chain reaction was used to analyze the expression of proinflammatory and antiinflammatory cytokines in ex vivo fluorescence‐activated cell sorted CTLA‐4+ and CTLA‐4− T helper cells from the peripheral blood and SF of RA patients. T helper cells were also analyzed for cytokine expression in vitro after the blockade of CTLA‐4 by anti–CTLA‐4 Fab fragments or of B7 (CD80/CD86) molecules by CTLA‐4Ig. Results CTLA‐4+ T helper cells were unambiguously present in the SF of all RA patients examined, and they expressed increased amounts of interferon‐γ (IFNγ), interleukin‐17 (IL‐17), and IL‐10 as compared to CTLA‐4− T helper cells. The selective blockade of CTLA‐4 in T helper cells from the SF in vitro led to increased levels of IFNγ, IL‐2, and IL‐17. The concomitant blockade of CD28 and CTLA‐4 in T helper cells from RA SF by CTLA‐4Ig in vitro resulted in reduced levels of the proinflammatory cytokines IFNγ and IL‐2 and increased levels of the antiinflammatory cytokines IL‐10 and transforming growth factor β. Conclusion Our ex vivo and in vitro results demonstrate that the CTLA‐4/CD28 axis constitutes a drug target for not only the systemic, but potentially also the local, application of the costimulation blocking agent CTLA‐4Ig for the treatment of RA.